Atmosphere‐Ionosphere (A‐I) Coupling as Viewed by ICON: Day‐to‐Day Variability Due to Planetary Wave (PW)‐Tide Interactions. Issue 6 (21st June 2021) - Forbes, Jeffrey M.; Zhang, Xiaoli; Heelis, Roderick; Stoneback, Russell; Englert, Christoph R.; Harlander, John M.; Harding, Brian J.; Marr, Kenneth D.; Makela, Jonathan J.; Immel, Thomas J.
Abstract: Coincident Ionospheric Connections Explorer (ICON) measurements of neutral winds, plasma drifts and total ion densities (:=Ne, electron density) are analyzed during January 1–21, 2020 to reveal the relationship between neutral winds and ionospheric variability on a day‐to‐day basis. Atmosphere‐ionosphere (A‐I) connectivity inevitably involves a spectrum of planetary waves (PWs), tides and secondary waves due to wave‐wave nonlinear interactions. To provide a definitive attribution of dynamical origins, the current study focuses on a time interval when the longitudinal wave‐4 component of the E‐region winds is dominated by the eastward‐propagating diurnal tide with zonal wavenumber s = −3 (DE3). DE3 is identified in winds and ionospheric parameters through its characteristic dependence on local solar time and longitude as ICON's orbit precesses. Superimposed on this trend are large variations in low‐latitude DE3 wave‐4 zonal winds (±40 ms −1 ) and topside F‐region equatorial vertical drifts at periods consistent with 2‐days and 6‐days PWs, and a ∼3‐day ultra‐fast Kelvin wave (UFKW), coexisting during this time interval; the DE3 winds, dynamo electric fields, and drifts are modulated by these waves. Wave‐4 variability in Ne is of order 25%–35%, but the origins are more complex, likely additionally reflecting transport by ∼20–25 ms −1 wave‐4 in‐situ winds containing strong signatures of DE3 interactions with ambient diurnal Sun‐synchronous winds and ion drag. These results are the first to show a direct link between day‐to‐day wave‐4 variability in contemporaneously measured E‐region neutral winds and F‐region ionospheric drifts and electron densities. Key Points: Coincident Ionospheric Connections Explorer measurements of neutral winds, plasma drifts and total ion densities (:=Ne) are analyzed during January 1–21, 2020 We show for the first time that planetary wave winds modulate DE3 and produce longitudinal wave‐4 variations in F‐region vertical drifts ∼±10 ms −1, Ne ∼ ±30% Measured F‐region wave‐4 winds suggest that SPW4, SE2 & DW5 arising from tide‐tide and tide‐ion drag interactions also contribute to Ne variability